2020
DOI: 10.3389/fonc.2020.01053
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and OXPHOS Activities Quantified by Temporal ex vivo Analysis Display Patient-Specific Metabolic Vulnerabilities in Human Breast Cancers

Abstract: Research on mitochondrial metabolism and respiration are rapidly developing areas, however, efficient and widely accepted methods for studying these in solid tumors are still missing. Here, we developed a new method without isotope tracing to quantitate time dependent mitochondrial citrate efflux in cell lines and human breast cancer samples. In addition, we studied ADP-activated respiration in both of the sample types using selective permeabilization and showed that metabolic activity and respiration are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Our recent studies revealed remarkable differences in the regulation of outer mitochondrial membrane (OMM) permeability between cultured tumor cells and clinical material from cancer patients (5,43). Comparative analysis of the biopsy or surgical cancer material and surrounding healthy tissue showed almost unchanged glycolytic activity and upregulation of OXPHOS in CRC, which is inconsistent with the data obtained by using cell culture (43)(44)(45)(46)(47). In addition, two widely used breast cancer cell lines MCF7 and MCF-MDA-231 failed to replicate mitochondrial function in respect to metabolic activity and OXPHOS as seen in respective human samples (43,46).…”
Section: Metabolic Reprogramming Of Colorectal Cancermentioning
confidence: 78%
See 1 more Smart Citation
“…Our recent studies revealed remarkable differences in the regulation of outer mitochondrial membrane (OMM) permeability between cultured tumor cells and clinical material from cancer patients (5,43). Comparative analysis of the biopsy or surgical cancer material and surrounding healthy tissue showed almost unchanged glycolytic activity and upregulation of OXPHOS in CRC, which is inconsistent with the data obtained by using cell culture (43)(44)(45)(46)(47). In addition, two widely used breast cancer cell lines MCF7 and MCF-MDA-231 failed to replicate mitochondrial function in respect to metabolic activity and OXPHOS as seen in respective human samples (43,46).…”
Section: Metabolic Reprogramming Of Colorectal Cancermentioning
confidence: 78%
“…Comparative analysis of the biopsy or surgical cancer material and surrounding healthy tissue showed almost unchanged glycolytic activity and upregulation of OXPHOS in CRC, which is inconsistent with the data obtained by using cell culture ( 43 47 ). In addition, two widely used breast cancer cell lines MCF7 and MCF-MDA-231 failed to replicate mitochondrial function in respect to metabolic activity and OXPHOS as seen in respective human samples ( 43 , 46 ).…”
Section: Metabolic Reprogramming Of Colorectal Cancermentioning
confidence: 99%
“…The best predictors for these states are determined by vimentin (VIM) and E-cadherin (CHD1) gene expression ratio combined with claudin 7 (CLDN7) expression using the TCGA breast cancer datasets ( 73 ) as well as the correlation of MMP2 expression to the progression of breast cancer to bone metastasis ( 74 ). Overexpression of the two mitochondrial proteins, citrate synthase (CS) and complex V subunit, ATP5C1 (or ATP5F1C), are described as markers for aggressiveness in triple negative breast cancer ( 75 , 76 ).…”
Section: Resultsmentioning
confidence: 99%
“…DCA has been shown to induce higher toxicity to cells if they have defective mitochondria [ 34 , 35 ]. In fact, MCF7 cells have been proven to transform glutamate and also pyruvate into citrate at a lower rate than MDA-MB-231 breast cancer cells [ 70 ], and their expression of complex II, III, and V is also lower than other breast cancer cell lines [ 71 ].…”
Section: Discussionmentioning
confidence: 99%